Genre Analysis of the Introduction Sections of Newsfile, a Ghanaian TV Talk Show - Ebenezer Agbaglo; Alimsiwen Elijah Ayaawan; Evelyn Owusu (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
In recent times, the language of mediatized genres has attracted much scholarly attention all over the world. However, little is known about the rhetorical structure and linguistic realisation of television talk shows in Ghana. This study, therefore, examined the Introduction sections of Newsfile, a popular television talk show telecast on JoyNews, a Ghanaian television station, to determine its schematic structure and linguistic realisations. Data for the study comprised five Introduction sections of the Newsfile aired after the 2016 general elections. The data were transcribed and analyzed based on the English for Specific Purposes (ESP) approach to genre analysis.  The findings revealed that the Introduction section of the talk show was characterized by ten moves (Greetings, Naming of Programme, The Seller, Naming the Host, Invitation of Viewers, Introduction of Subject, Signalling Commercial Break, Host’s Address, Introduction of Guests, and Introduction of Sponsors), with the Host’s Address and Introduction of Guests realized by steps. The study also revealed that while some of these moves were obligatory, others were optional. Additionally, it was revealed that there were recursions of some moves. Further analysis revealed the linguistic resources used in each of the moves. This study has implications for scholarship on talk shows especially in sub-Saharan Africa, genre studies, pedagogy, and further research.